2021
DOI: 10.3390/genes12020315
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Determination Cascade in the Silkworm

Abstract: In insects, sex determination pathways involve three levels of master regulators: primary signals, which determine the sex; executors, which control sex-specific differentiation of tissues and organs; and transducers, which link the primary signals to the executors. The primary signals differ widely among insect species. In Diptera alone, several unrelated primary sex determiners have been identified. However, the doublesex (dsx) gene is highly conserved as the executor component across multiple insect orders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…Thus, a possible function of AllWSEX2 and the transposase-like sequence located to the 3′ of AllWSEX2 should be further studied, including the possibility of their involvement in female transposon silencing. However, repression of transposable elements has been shown to participate in sex determination only in invertebrates (Yang et al, 2021); and transposable elements are over-expressed in testes of fish with no obvious association to sex determination (Dechaud et al, 2021).…”
mentioning
confidence: 99%
“…Thus, a possible function of AllWSEX2 and the transposase-like sequence located to the 3′ of AllWSEX2 should be further studied, including the possibility of their involvement in female transposon silencing. However, repression of transposable elements has been shown to participate in sex determination only in invertebrates (Yang et al, 2021); and transposable elements are over-expressed in testes of fish with no obvious association to sex determination (Dechaud et al, 2021).…”
mentioning
confidence: 99%
“…In Drosophila, mutation of Dart5 (homolog of Prmt5) leads to a failure in the sDMA modification of PIWIs and Tudors, which compromises their ability to interact with other proteins and to be properly localized in the cells, eventually resulting in severe defects in oogenesis [35,36]. However, our previous studies have shown that mutation of either PIWIs or Tudors basically barely affects male fertility in B, mori [52,53]. In this study, as mutation of BmPrmt5 does not affect the protein stability of Previous studies have demonstrated that morphology defects in the bundles of either eupyrene or apyrene sperm compromise their physiological function [14,16,54].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, 2020;S. Chen et al, 2020;Li et al, 2018;Yang et al, 2021). For example, BmMael is involved in the regulation of both morphs of sperm development, while BmPnldc1 is required for eupyrene sperm development.…”
Section: Morimentioning
confidence: 99%
“…Mutations in piRNA biogenesis pathway typically result in sterility with stereotypical phenotypes in the female or male germline (Juliano et al, 2011). In B. mori , the biochemical functions of the components involved in piRNA biogenesis such as PIWIs (Siwi and BmAgo3), and BmPnldc1, BmHen1 and BmPapi are well studied in ovary-derived cells (BmN) (Sakakibara and Siomi, 2018), and some of them have been physiologically characterized in vivo (Chen et al, 2019; K. Chen et al, 2020; S. Chen et al, 2020; Li et al, 2018; Yang et al, 2021). For example, BmMael is involved in the regulation of both morphs of sperm development, while BmPnldc1 is required for eupyrene sperm development.…”
Section: Introductionmentioning
confidence: 99%